Algorithms assistance of the car maneuvers during parallel and perpendicular parking - Manuel, Calequela João Tomé (2023)
A vehicular project must consider and guarantee the safety of the driver and third parties. As critical factors are the control of the action of the car's pedals (clutch, brake, accelerator) and the visual control of the blind spots (front, rear, left, right and laterals) that must be controlled simultaneously during the execution of a car parking maneuver. The development of a product in Industry 4.0 consists of the sequence of steps/processes used as metric evaluations in relation to time, economy, application and innovation. The positive sequence of computational simulations/tests in the Software-in-the-Loop (SIL) model reduces/eliminates the risk of obtaining an unsuccessful validation in the Hardware-in-the-Loop (HIL) model, aiming at the economy of electronic components or devices. The reduction of human effort, shorter maneuvering time during automatic parking of the car, and the guarantee of safety that provides comfort becomes an extra attraction for consumers to purchase the product; on the other hand a great challenge for the 4.0/automotive industry that must make the purchase price of the product (automatic maneuver assistance system for cars) accessible. However, this doctoral thesis, proposes and valid as solution the development of a software package integrated by 2 algorithms of maneuver of the automatic parking for cars, highlighted as: Parallel algorithms and perpendicular. The development of the algorithms was based on the (C) programming language and represented in (.m) as it is a type of easy-to-implement language, which ensures the correct functioning of most modules or communications buses of electric, hybrid, and autonomous cars. The tests were validated in the computational model Software-inthe-Loop (SIL) represented in 2D with help of Matlab/Simulink software. Therefore, the positive results attest to the veracity of the algorithms based on the mathematical/geometric equations designed to control the maneuvers of the car during parking.